Probing BEC phase fluctuations with atomic quantum dots - Bruderer, M; Jaksch, D (Institute of Physics Publishing Ltd., 2006)
We consider the dephasing of two internal states |0> and |1> of a trapped impurity atom, a so-called atomic quantum dot (ACD), where only state |1> couples to a Bose-Einstein condensate (BEC). A direct relation between the dephasing of the internal states of the AQD and the temporal phase fluctuations of the BEC is established. Based on this relation we suggest a scheme to probe BEC phase fluctuations non-destructively via dephasing measurements of the AQD. In particular, the scheme allows to trace the dependence of the phase fluctuations on the trapping geometry of the BEC.